Acute thermal stress alters sperm swimming activity, viability, and gene expression in blue catfish, Ictalurus furcatus - Kaylan M. Price; Brian G. Bosworth; Samitha S.N. Liyanage; Jason W. Abernathy; Benjamin H. Beck; Luke A. Roy; Timothy J. Bruce; Rex A. Dunham; Ian A.E. Butts (Theriogenology, 2026)

Oceanward surface transport from the NW African upwelling zone by coastal jet detachment and filaments - Luuk Rader; Borja Aguiar-González; Timothy David Price; Daura Vega-Moreno; Eugenio Fraile-Nuez; Francisco Machín (Frontiers in Marine Science, 2026)
The oceanward surface transport of particles, including marine litter, from the northwestern African upwelling zone is influenced by multiple interacting physical processes. This study applies the OceanParcels Lagrangian framework to investigate the mechanisms that may contribute to oceanward surface transport in this region, motivated by the hypothesis that the northwestern African upwelling system could represent a potential source of marine litter in the vicinity of the Canary Islands. The simulations suggest that the coastal jet stream and its detachment, upwelling filaments, and Stokes drift play key roles in shaping particle trajectories. In particular, coastal jet detachment appears to organize surface transport into narrow, oceanward-oriented particle corridors, while upwelling filaments may provide additional offshore export pathways. Stokes drift introduces a predominantly southward deflection that can reduce or modulate oceanward advection and enhance alongshore transport. These results provide a process-based, model-derived first assessment of previously understudied oceanward transport corridors in the NW African upwelling system. They are consistent with the hypothesis that this region may contribute to surface tracer transport toward the Canary Islands. However, caution is required when extrapolating these findings to marine debris, as windage is not included and may significantly alter transport pathways. Continued investigation, including observational validation and improved surface forcing representations, will help further constrain the mechanisms shaping particle transport in the NW African upwelling system.

Field efficacy, adult emergence, and yield evaluation of the corn rootworm transgenic events in Vorceed™ Enlist® corn and SmartStax® PRO hybrid corn against corn rootworms (Coleoptera: Chrysomelidae) - Timothy Mabry; Jeffrey Klever; Christianah Oladoye; Timothy Nowatzki; James Bing; Amit Sethi; Michael Price; Lu Liu (Crop Protection, 2025)

A decision support tool for assessing entanglement risk to protected species from fixed-gear fisheries with applications to North Atlantic right whales (Eubalaena glacialis) in the Northwest Atlantic - Burton Shank; Alicia S. Miller; Laura Solinger; Michael J. Asaro; Douglas Sigourney; Alessandra Huamani; Marisa L. Trego; Crystal Franco; Jason J. Roberts; Jeffrey D. Walker; André L. Price; Mareike D. Duffing Romero; et al. (Frontiers in Marine Science, 2025)
Entanglement is one of the primary anthropogenic threats to the North Atlantic right whale ( Eubalaena glacialis ; right whale) whose habitat overlaps fixed-gear fishing grounds in the Northwest Atlantic with entanglements representing around half of the mortality and serious injury incidents. Right whale mortality has reached levels that require intervention under the Marine Mammal Protection Act, creating the need for a tool that can compare the relative benefits of risk reduction management measures under consideration. To address this need, National Marine Fisheries Service developed a Decision Support Tool (DST) which has undergone continued development since 2019 and is introduced here as the Woods Hole Analysis of Line Entanglement (WHALE) DST. This tool calculates relative risk as the product of (1) the density of endlines associated with fixed-gear fishing at a given location and month, (2) the entanglement severity that endlines pose based on the specific configuration of the gear, and (3) the estimated density of right whales at the given location and month. The model is novel in its capacity to quantify reductions in entanglement risk by simultaneously assessing a variety of overlapping management actions such as time/area closures, weakening of rope, and other adaptations of gear configurations that reduce endlines or make them less dangerous. We demonstrate the functionality of the WHALE DST by applying management actions implemented in 2021. While originally developed for right whale conservation, the WHALE DST is adaptable for evaluating spatiotemporal entanglement risk reduction for other protected species management and marine spatial planning activities.

Monitoring Resilience in Coastal Systems: A Comprehensive Assessment - Emma Imen Turki; Elena Ojeda; Ernesto Tonatiuth Mendoza; Gabriela Medellín; Timothy D. Price; Edward Salameh; Xiao Hua Wang; Li Li; Gemma L. Franklin; Alec Torres-Freyermuth (Journal of Marine Science and Engineering, 2025)
This work, conducted within the framework of the international network CRESTE (Coastal Resilience Using Satellites), examines the role of resilience in monitoring coastal evolution across diverse environments in Europe (France, The Netherlands), America (Mexico), Asia (China), and Oceania (Australia). High-resolution morphological datasets, derived from in situ measurements and video monitoring systems, were analyzed for wave- and tide-dominated beaches influenced by both climatic drivers and anthropogenic pressures. Findings indicate that beach resilience is strongly linked to system resistance, which depends on the intensity of climate drivers, including storm frequency, and site-specific conditions related to the type of sediment and its availability, and the presence of anthropogenic activities including coastal structures (e.g., Normandy, Yucatán) and shoreface nourishments (Netherlands). In Batemans Bay (Australia) and Hangzhou Bay (China), assessing the resilience is particularly challenging due to the combined influence of multiple drivers, fluvial inputs, and urban development. Accurate monitoring of coastal resilience across timescales requires accounting for long-term morphological, ecological, and socio-economic processes. This can be enhanced through satellite observations, which, when integrated with in situ measurements, numerical modeling, and artificial intelligence, support a more comprehensive assessment of resilience and refine projections under future climate change and sea-level rise; representing a key focus for further works.

Drinking water sources, quality, and associated health outcomes in Appalachian Virginia: A risk characterization study in two counties - Alasdair Cohen; Md Rasheduzzaman; Bethesda O'Connell; Teresa Brown; Mami Taniuchi; Leigh-Anne Krometis; Alan Hubbard; Phillip Scheuerman; Marc Edwards; Amanda Darling; Blaine Pennala; Sarah Price; et al. (International Journal of Hygiene and Environmental Health, 2024)

From reflection diaries to practical guidance for transdisciplinary research: learnings from a Kenyan air pollution project - Heather D. Price; Cressida J. Bowyer; Patrick Büker; Cindy M. Gray; Matthew Hahn; Fiona Lambe; Miranda Loh; Alexander J. Medcalf; Timothy Kamau Njoora; Charlotte Waelde; Megan Wainwright; Sarah E. West (Sustainability Science, 2023)
Transdisciplinary research (TDR) approaches have been cited as essential for overcoming the intractable sustainability challenges that the world is currently facing, including air pollution, water management and climate change. However, such approaches can be difficult to undertake in practice and can consequently fail to add value. Therefore, examples of what works in practice (and what does not) are helpful to guide future research. In this study, we used a conceptual TDR framework as the basis to examine and evaluate the strengths and weaknesses of our approach in a project exploring air pollution in an informal settlement in Nairobi, Kenya. Reflection diaries exploring experiences of participation in the project were undertaken by the project team (comprising academic and community partners) at multiple time points throughout the project. These reflection diaries played an important role in evaluation and for providing space for team learning. Diaries were thematically coded according to the TDR framework to explore aspects of the project that worked well, and areas which presented challenges. We draw upon our reflections, and the extant literature, to make practical recommendations for researchers undertaking TDR projects in future. Recommendations focus on three key project stages (pre-funding, funded period, post-funding) and include; building the team in a way that includes all key stakeholders in relevant and appropriate roles, giving everyone sufficient time to work on the project, and ensuring regular and open communication. Building these recommendations into the design and delivery of transdisciplinary sustainability science projects will support progress towards achieving the Sustainable Development Goals (SDGs).

Quantification of meteorological drought risks between 1.5 °C and 4 °C of global warming in six countries - Jeff Price; Rachel Warren; Nicole Forstenhäusler; Craig Wallace; Rhosanna Jenkins; Timothy J. Osborn; D. P. Van Vuuren (Climatic Change, 2022)
We quantify the projected impacts of alternative levels of global warming upon the probability and length of severe drought in six countries (China, Brazil, Egypt, Ethiopia, Ghana and India). This includes an examination of different land cover classes, and a calculation of the proportion of population in 2100 (SSP2) at exposed to severe drought lasting longer than one year. Current pledges for climate change mitigation, which are projected to still result in global warming levels of 3 °C or more, would impact all of the countries in this study. For example, with 3 °C warming, more than 50% of the agricultural area in each country is projected to be exposed to severe droughts of longer than one year in a 30-year period. Using standard population projections, it is estimated that 80%-100% of the population in Brazil, China, Egypt, Ethiopia and Ghana (and nearly 50% of the population of India) are projected to be exposed to a severe drought lasting one year or longer in a 30-year period. In contrast, we find that meeting the long-term temperature goal of the Paris Agreement, that is limiting warming to 1.5 °C above pre-industrial levels, is projected to greatly benefit all of the countries in this study, greatly reducing exposure to severe drought for large percentages of the population and in all major land cover classes, with Egypt potentially benefiting the most.

Momentum and Turbulent Transport in Sparse, Organized Vegetative Canopies - Gregory Torkelson; Timothy A. Price; Rob Stoll (Boundary-Layer Meteorology, 2022)

Quantifying risks avoided by limiting global warming to 1.5 or 2 °C above pre-industrial levels - Rachel Warren; Oliver Andrews; Sally Brown; Felipe J. Colón-González; Nicole Forstenhäusler; David E. H. J. Gernaat; P. Goodwin; Ian Harris; Yi He; Chris Hope; Desmond Manful; Timothy J. Osborn; et al. (Climatic Change, 2022)
The Paris Agreement aims to constrain global warming to ‘well below 2 °C’ and to ‘pursue efforts’ to limit it to 1.5 °C above pre-industrial levels. We quantify global and regional risk-related metrics associated with these levels of warming that capture climate change–related changes in exposure to water scarcity and heat stress, vector-borne disease, coastal and fluvial flooding and projected impacts on agriculture and the economy, allowing for uncertainties in regional climate projection. Risk-related metrics associated with 2 °C warming, depending on sector, are reduced by 10–44% globally if warming is further reduced to 1.5 °C. Comparing with a baseline in which warming of 3.66 °C occurs by 2100, constraining warming to 1.5 °C reduces these risk indicators globally by 32–85%, and constraining warming to 2 °C reduces them by 26–74%. In percentage terms, avoided risk is highest for fluvial flooding, drought, and heat stress, but in absolute terms risk reduction is greatest for drought. Although water stress decreases in some regions, it is often accompanied by additional exposure to flooding. The magnitude of the percentage of damage avoided is similar to that calculated for avoided global economic risk associated with these same climate change scenarios. We also identify West Africa, India and North America as hotspots of climate change risk in the future.

Rapid evolutionary divergence of a songbird population following recent colonization of an urban area - Guillermo Friis; Jonathan W. Atwell; Adam M. Fudickar; Timothy J. Greives; Pamela J. Yeh; Trevor D. Price; Ellen D. Ketterson; Borja Milá (Molecular Ecology, 2022)
Colonization of a novel environment by a few individuals can lead to rapid evolutionary change, yet there is scarce evidence of the relative contributions of neutral and selective factors in promoting divergence during the early stages of colonization. Here we explore the role of neutral and selective forces in the divergence of a unique urban population of the dark‐eyed junco ( Junco hyemalis ), which became established on the campus of the University of California at San Diego (UCSD) in the early 1980s. Previous studies based on microsatellite loci documented significant genetic differentiation of the urban population as well as divergence in phenotypic traits relative to nearby montane populations, yet the geographical origin of the colonization and the contributing factors remained uncertain. Our genome‐wide single nucleotide polymorphism data set confirmed the marked genetic differentiation of the UCSD population, and we identified the coastal subspecies pinosus from central California as its sister group instead of the neighbouring mountain population. Demographic inference recovered a separation from pinosus as recent as 20–32 generations ago after a strong bottleneck, suggesting a role for drift in genetic differentiation. However, we also found significant associations between habitat variables and genome‐wide variants linked to functional genes, some of which have been reported as potentially adaptive in birds inhabiting modified environments. These results suggest that the interplay between founder events and selection may result in rapid shifts in neutral and adaptive loci across the genome, and reveal the UCSD junco population as a case of contemporary evolutionary divergence in an anthropogenic environment.

Evaluation of pharmacogenomics and hepatic nuclear imaging–related covariates by population pharmacokinetic models of irinotecan and its metabolites - Zheng Liu; Jennifer H. Martin; Winston Liauw; Sue-Anne McLachlan; Emma Link; Anetta Matera; Michael Thompson; Michael Jefford; Rod J. Hicks; Carleen Cullinane; Athena Hatzimihalis; Ian Campbell; et al. (European Journal of Clinical Pharmacology, 2022)

Quantification of impacts between 1.5 and 4 °C of global warming on flooding risks in six countries - Yi He; Desmond Manful; Rachel Warren; Nicole Forstenhäusler; Timothy J. Osborn; Jeff Price; Rhosanna Jenkins; Craig Wallace; Dai Yamazaki (Climatic Change, 2022)
We project climate change induced changes in fluvial flood risks for six global warming levels between 1.5 and 4 °C by 2100, focusing on the major river basins of six countries. Daily time series of precipitation, temperature and monthly potential evapotranspiration were generated by combining monthly observations, daily reanalysis data and projected changes in the five CMIP5 GCMs also selected in the ISI-MIP fast track project. These series were then used to drive the HBV hydrological model and the CaMa-Flood hydrodynamic model to simulate river discharge and flood inundation. Our results indicate that return periods of 1 in 100-year floods in the late twentieth century (Q100-20C) are likely to decrease with warming. At 1.5 °C warming, 47%, 66%, 27%, 65%, 62% and 92% of the major basin areas in Brazil, China, Egypt, Ethiopia, Ghana and India respectively experience a decrease in the return period of Q100-20C, increasing to 54%, 81%, 28%, 82%, 86% and 96% with 4 °C warming. The decrease in return periods leads to increased number of people exposed to flood risks, particularly with 4 °C warming, where exposure in the major river basin areas in the six countries increases significantly, ranging from a doubling (China) to more than 50-fold (Egypt). Limiting warming to 1.5 °C would avoid much of these increased risks, resulting in increases ranging from 12 to 1266% for the 6 countries.

Temporal rarity is a better predictor of local extinction risk than spatial rarity - Peter A. Wilfahrt; Ashley L. Asmus; Eric W. Seabloom; Jeremiah A. Henning; Peter Adler; Carlos A. Arnillas; Jonathan D. Bakker; Lori Biederman; Lars A. Brudvig; Marc Cadotte; Pedro Daleo; Anu Eskelinen; et al. (Ecology, 2021)
Spatial rarity is often used to predict extinction risk, but rarity can also occur temporally. Perhaps more relevant in the context of global change is whether a species is core to a community (persistent) or transient (intermittently present), with transient species often susceptible to human activities that reduce niche space. Using 5–12 yr of data on 1,447 plant species from 49 grasslands on five continents, we show that local abundance and species persistence under ambient conditions are both effective predictors of local extinction risk following experimental exclusion of grazers or addition of nutrients; persistence was a more powerful predictor than local abundance. While perturbations increased the risk of exclusion for low persistence and abundance species, transient but abundant species were also highly likely to be excluded from a perturbed plot relative to ambient conditions. Moreover, low persistence and low abundance species that were not excluded from perturbed plots tended to have a modest increase in abundance following perturbance. Last, even core species with high abundances had large decreases in persistence and increased losses in perturbed plots, threatening the long‐term stability of these grasslands. Our results demonstrate that expanding the concept of rarity to include temporal dynamics, in addition to local abundance, more effectively predicts extinction risk in response to environmental change than either rarity axis predicts alone.

Inhibition of Erwinia amylovora by Bacillus nakamurai - Timothy D. Leathers; Lauren P. Saunders; Michael J. Bowman; Neil P. J. Price; Kenneth M. Bischoff; Joseph O. Rich; Christopher D. Skory; Melinda S. Nunnally (Current Microbiology, 2020)

Research priorities for managing the impacts and dependencies of business upon food, energy, water and the environment - Jonathan M. H. Green; Gemma R. Cranston; William J. Sutherland; Hannah R. Tranter; Sarah J. Bell; Tim G. Benton; Eva Blixt; Colm Bowe; Sarah Broadley; Andrew Brown; Chris Brown; Neil Burns; et al. (Sustainability Science, 2017)

Production of anti-streptococcal liamocins from agricultural biomass by Aureobasidium pullulans - Timothy D. Leathers; Neil P. J. Price; Pennapa Manitchotpisit; Kenneth M. Bischoff (World Journal of Microbiology and Biotechnology, 2016)

Integrated environmental assessment to explore water resources management in Al Jabal Al Akhdar, Sultanate of Oman - Mohammed Saif Al-Kalbani; Martin Francis Price; Timothy O’Higgins; Mushtaque Ahmed; Asma Abahussain (Regional Environmental Change, 2016)

Evidence for Alzheimer’s disease-linked synapse loss and compensation in mouse and human hippocampal CA1 pyramidal neurons - Krystina M. Neuman; Elizabeth Molina-Campos; Timothy F. Musial; Andrea L. Price; Kwang-Jin Oh; Malerie L. Wolke; Eric W. Buss; Stephen W. Scheff; Elliott J. Mufson; Daniel A. Nicholson (Brain Structure and Function, 2015)

Production of novel types of antibacterial liamocins by diverse strains of Aureobasidium pullulans grown on different culture media - Timothy D. Leathers; Neil P. J. Price; Kenneth M. Bischoff; Pennapa Manitchotpisit; Christopher D. Skory (Biotechnology Letters, 2015)

Enzymatic modification of schizophyllan - Timothy D. Leathers; Nongnuch Sutivisedsak; Melinda S. Nunnally; Neil P. J. Price; April M. Stanley (Biotechnology Letters, 2015)

Erratum to: Aureobasidium pullulans as a source of liamocins (heavy oils) with anticancer activity - Pennapa Manitchotpisit; Ramida Watanapokasin; Neil P. J. Price; Kenneth M. Bischoff; Malatee Tayeh; Sudarat Teeraworawit; Saranya Kriwong; Timothy D. Leathers (World Journal of Microbiology and Biotechnology, 2014)

Aureobasidium pullulans as a source of liamocins (heavy oils) with anticancer activity - Pennapa Manitchotpisit; Ramida Watanapoksin; Neil P. J. Price; Kenneth M. Bischoff; Malatee Tayeh; Sudarat Teeraworawit; Saranya Kriwong; Timothy D. Leathers (World Journal of Microbiology and Biotechnology, 2014)

Bacillus spp. Produce Antibacterial Activities Against Lactic Acid Bacteria that Contaminate Fuel Ethanol Plants - Pennapa Manitchotpisit; Kenneth M. Bischoff; Neil P. J. Price; Timothy D. Leathers (Current Microbiology, 2013)

Prediagnostic concentrations of plasma genistein and prostate cancer risk in 1,605 men with prostate cancer and 1,697 matched control participants in EPIC - Ruth C. Travis; Naomi E. Allen; Paul N. Appleby; Alison Price; Rudolf Kaaks; Jenny Chang-Claude; Heiner Boeing; Krasimira Aleksandrova; Anne Tjønneland; Nina Føns Johnsen; Kim Overvad; J. Ramón Quirós; et al. (Cancer Causes & Control, 2012)

Heavy oils produced by Aureobasidium pullulans - Pennapa Manitchotpisit; Neil P. J. Price; Timothy D. Leathers; Hunsa Punnapayak (Biotechnology Letters, 2011)

Epidemiology of neuroendocrine cancers in an Australian population - Colin Luke; Timothy Price; Amanda Townsend; Christos Karapetis; Dusan Kotasek; Nimit Singhal; Elizabeth Tracey; David Roder (Cancer Causes & Control, 2010)

Co-production of Schizophyllan and Arabinoxylan from Corn Fiber - Timothy D. Leathers; Melinda S. Nunnally; Neil P. Price (Biotechnology Letters, 2006)

Magnesian andesite and dacite lavas from Mt. Shasta, northern California: products of fractional crystallization of H2O-rich mantle melts - Timothy L. Grove; Michael B. Baker; Richard C. Price; Stephen W. Parman; Linda T. Elkins-Tanton; Nilanjan Chatterjee; Othmar Mntener (Contributions to Mineralogy and Petrology, 2005)

The potential use of raman mapping to investigate in vitro deposition of combination pressurized metered-dose inhalers - D. Fraser Steele; Paul M. Young; Robert Price; Timothy Smith; Stephen Edge; David Lewis (The AAPS Journal, 2004)

Observations of a new source of coral mortality along the Kenyan coast - Timothy R. McClanahan; Shawn M. McLaughlin; Joanne E. Davy; William H. Wilson; Esther C. Peters; Kathy L. Price; Joseph Maina (Hydrobiologia, 2004)